A polynomial model and multi-objective optimization based travel curve planning method for direct motor drive actuators - Wang, Xiao; Wu, Xusheng; Xiao, Xi; Xie, Yulong (IEEE access, 2023)
The direct-drive actuator of permanent magnet synchronous motor is an innovative application of servo technology in the field of high-voltage circuit breaker, which can drive the movable contact of high-voltage switch to complete the breaking and closing operation according to the optimal path. At present, the travel curve of motor direct-drive actuator cannot match the mechanism and system characteristics effectively, and there is no systematic planning method. To address the travel curve planning of motor direct-drive actuator, a travel curve planning method based on polynomial model and multi-objective optimization is proposed. Firstly, the kinematic and kinetic models of motor direct-drive actuator loads are established, then the polynomial model is used to generate the travel curve clusters, and finally, a multi-objective optimization algorithm is constructed based on the motor direct-drive actuator and circuit breaker operation indexes, and the multi-objective optimization algorithm weights are optimized by combining with particle swarm algorithm, and the best travel curve is selected. Simulation and experimental studies show that the method can achieve stable and reliable operation of the motor direct-drive operating mechanism, and can achieve 11.2% energy consumption optimization compared with existing methods, improve the overall power density of the system, and further reduce the overall running time and extend the service life of the dynamic contacts during continuous operation.